2015
DOI: 10.1002/cncr.29773
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and model for predicting toxicity‐related treatment discontinuation in patients with metastatic renal cell carcinoma treated with vascular endothelial growth factor–targeted therapy: Results from the International Metastatic Renal Cell Carcinoma Database Consortium

Abstract: BACKGROUND: Vascular endothelial growth factor (VEGF)-targeted therapies are standard treatment for metastatic renal cell carcinoma (mRCC); however, toxicities can lead to drug discontinuation, which can affect patient outcomes. This study was aimed at identifying risk factors for toxicity and constructing the first model to predict toxicity-related treatment discontinuation (TrTD) in mRCC patients treated with VEGF-targeted therapies. METHODS: The baseline characteristics, treatment outcomes, and toxicity dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…However, diverse genetic alterations are linked to renal cancer progression and to our ability to predict its risk [ 13 , 23 ]. Targeted therapies incorporating inhibitors of the vascular endothelial growth factor (VEGF) pathway is the major treatment for patients with metastatic RCC [ 18 , 20 , 49 ]. For example, anti-angiogenic drugs such as sunitinib can nullify alterations in the microvascular properties of some human cancers [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, diverse genetic alterations are linked to renal cancer progression and to our ability to predict its risk [ 13 , 23 ]. Targeted therapies incorporating inhibitors of the vascular endothelial growth factor (VEGF) pathway is the major treatment for patients with metastatic RCC [ 18 , 20 , 49 ]. For example, anti-angiogenic drugs such as sunitinib can nullify alterations in the microvascular properties of some human cancers [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, frequency and severity of major toxic events leading to dose reductions and discontinuations differ according to patient age [3,13]. A study [26] from the International Metastatic Renal Cell Cancer database identified older age to be a predictive factor of toxicity-related discontinuations of treatment among patients treated with targeted therapeutic agents. Likewise, Miyake et al [27] found that the proportion of older patients undergoing a modified sunitinib regimen, whereby the initial dose was reduced due to toxicity, was larger when compared with younger adults.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic kidney disease was already reported to be significantly associated with toxicity-related treatment discontinuation [22, 23]. Hyponatremia is well-known to be correlated with poor prognosis in RCC patients treated with molecular-targeted therapy [2426].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, discontinuation of sunitinib therapy was significantly correlated with the presence of hyponatremia and renal impairment. Chronic kidney disease was already reported to be significantly associated with toxicity-related treatment discontinuation [ 22 , 23 ]. Hyponatremia is well-known to be correlated with poor prognosis in RCC patients treated with molecular-targeted therapy [ 24 26 ].…”
Section: Discussionmentioning
confidence: 99%